Expression Profile of Defense Genes in Rice Lines Pyramided with Resistance Genes Against Bacterial Blight, Fungal Blast and Insect Gall Midge - Dhanasekar Divya; Kanaparthi Ratna Madhavi; Muralidharan Ayyappa Dass; Roshan Venkata Maku; Garladinne Mallikarjuna; Raman Meenakshi Sundaram; Gouri Sankar Laha; Ayyagari Phani Padmakumari; Hitendra Kumar Patel; Madamsetty Srinivas Prasad; Ramesh Venkata Sonti; Jagadish Sanmallappa Bentur (Rice, 2018)
Abstract Background Rice, a major food crop of the world, endures many major biotic stresses like bacterial blight (BB), fungal blast (BL) and the insect Asian rice gall midge (GM) that cause significant yield losses. Progress in tagging, mapping and cloning of several resistance (R) genes against aforesaid stresses has led to marker assisted multigene introgression into elite cultivars for multiple and durable resistance. However, no detailed study has been made on possible interactions among these genes when expressed simultaneously under combined stresses. Results Our studies monitored expression profiles of 14 defense related genes in 11 rice breeding lines derived from an elite cultivar with different combination of R genes against BB, BL and GM under single and multiple challenge. Four of the genes found implicated earlier under combined GM and BB stress were confirmed to be induced (≥ 2 fold) in stem tissue following GM infestation; while one of these, cytochrome P450 family protein, was also induced in leaf in plants challenged by either BB or BL but not together. Three of the genes highlighted earlier in plants challenged by both BB and BL were also found induced in stem under GM challenge. Pi54 the target R gene against BL was also found induced when challenged by GM. Though expression of some genes was noted to be inhibited under combined pest challenge, such effects did not result in compromise in resistance against any of the target pests. Conclusion While R genes generally tended to respond to specific pest challenge, several of the downstream defense genes responded to multiple pest challenge either single, sequential or simultaneous, without any distinct antagonism in expression of resistance to the target pests in two of the pyramided lines RPNF05 and RPNF08.